Entre espaces domestiques et « espaces domestiqués » : « L’autonomisation intime » des étudiantes en Turquie - Tuğba Gökduman (L’Année du Maghreb)
This article focuses on the familial, social and institutional issues related to the construction of a form of “intimate autonomy” by young women in the context of contemporary Turkey. In this article, “intimate autonomy” refers to the idea that the individual is defined as the “author of their action” in their private and sexual life. Young unmarried women, often viewed as potential sexual victims or corrupters of the moral order, are subject to surveillance in the name of “protection.” The family is the main structure responsible for this “protection”, and the domestic space reproduces mechanisms of control that aim to regulate young women’s bodies and sexualities. But how is control exercised when young woman physically moves away from family’s surveillance? The case of female students going to Istanbul for their university studies provides a relevant framework for the study of this question. The article makes the hypothesis that this mobility into the city, which is considered at first sight as an escape from the dominant sexual norms and from parental control, does not however mean a linear journey towards sexual emancipation. Student accommodations play an important role here. In order to shed light on the relationship between intimacy, space, young women and structures of control, the article first examines the power relations within the domestic space by describing the leeway available to young women living with their parents. Then, the departure to Istanbul and the new living spaces (student dormitories and (co)rentals) are presented. These residential spaces are regulated by institutions which are in charge of maintaining the moral order and of undertaking the role hold by families in regards to the moral “protection” of women. I call these spaces “domesticated spaces” where “taming” women’s sexuality is at play in the absence of parental control. I take inspiration from the researches of Suad Joseph (1997) who shows the fluidity of boundaries between what she defines as the governmental, non-governmental and domestic spaces, to explain the permeability of moral values from one space to another. The patriarchal “domestication” of women’s sexuality and of private spaces is not unanswered, thus the article analyzes the tactics of circumvention and so-called conformism. Through some examples taken from my fieldwork, I illustrate how individual agency and daily resistance are articulated with the respect for the collective morality. Finally, the non-linearity of sexual emancipation, the transition to adulthood and the evolution of gender and intergenerational relations is studied through the following of the back-and-forth journeys of young women between domestic and domesticated spaces. The article concludes that the rules of these spaces do not refrain women to search for ways leading to sexual emancipation. It also underlines that these women construct their individuality and their access to sexuality at the crossroads of different sexual norms and moral expectations. Another important conclusion is made on the changing of power structures, especially within the parental house where family relationships are marked simultaneously by conflict, divergence, compromise, negotiation, solidarity and affection. In this regard, the article takes into account the moving nature of relationships and of spaces. This article uses some of the data I collected during a master’s research at the EHESS. It draws from a sociological survey conducted between 2018-2020 among young women living in Istanbul without their families. These women, most of them being heterosexual and aged between 20-25, were mainly issued from middle-class families from different towns and villages in Turkey. At the time of my enquiry, they were students or recent graduates. They had integrated public or private universities in Istanbul and lived in student dormitories or in (co)rentals. The field survey consisted in conducting semi-structured individual interviews bringing together questions about their experience of leaving the family home and settling in Istanbul, but also about the evolution of gender and family relations following student mobility to Istanbul. These interviews were accompanied by observations and informal conversations which took place in different spaces of student socialization, such as university campuses, cafes, bars, or nightclubs.